2022
DOI: 10.1002/smll.202203334
|View full text |Cite
|
Sign up to set email alerts
|

A Dual‐Function Sensor for Highly Sensitive Detection of Flame and Humidity

Abstract: Early warning sensors rapidly monitor critical temperatures, humidity, and fires, which are crucial to reduce or avoid natural disasters in complex environments, such as fire or water disasters. Here, a highly sensitive, readable, and dual‐functional sensor is designed for a fast‐response fire alarm and rapid humidity detection based on sustainable biological films (named MSCG films). The MSCG films are composed of grafted sisal nanofibers (MgC), silk nanofibers, graphene, and citric acid (CA). After crosslink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…This circuit can be regarded as a simple strain sensor for recording the relative resistance of the hydrogels under different strains and times. Eq was used to calculate the relative resistance change (Δ R / R 0 ) normalΔ R / R 0 .25em ( % ) = ( R R 0 ) / R 0 × 100 % where R 0 and R are the resistance of the original sample and the sample under applied strain, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This circuit can be regarded as a simple strain sensor for recording the relative resistance of the hydrogels under different strains and times. Eq was used to calculate the relative resistance change (Δ R / R 0 ) normalΔ R / R 0 .25em ( % ) = ( R R 0 ) / R 0 × 100 % where R 0 and R are the resistance of the original sample and the sample under applied strain, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…After turning off the light power, the temperature quickly falls down to 29 °C within 40 s. Therefore, the composite foam, by the virtue of lightweight and broadband high-efficiency photothermal features, can also be used to convert light into heat and apply in various complex and harsh conditions. [58,65,66]…”
Section: Light Absorption and Light-driven Shape Memory Properties Of...mentioning
confidence: 99%
“…In recent 5 years, the carbon-based nanomaterials have been widely used to construct smart fire warning sensors by means of their transformation of electric performance under high temperatures. The reported materials include graphene, carbon nanotubes, and Ti 3 C 2 MXene. For example, Wang et al reported a fire-resistant cotton fabric (CF) that was coated with MXene nanosheets and carboxymethyl chitosan (CCS). Benefiting from the thermoelectric characteristic of the MXene nanosheet, MXene/CCS@CF triggered the fire alarm in 3.8 s upon exposure to the flame.…”
Section: Introductionmentioning
confidence: 99%